A 1μW-to-158μW Output Power Pseudo Open-Loop Boost DC-DC with 86.7% Peak Efficiency using Frequency-Programmable Oscillator and Hybrid Zero Current Detection - Chen, Xiaolong; Gong, Enbin; Zhang, Hao; Ye, Le; Huang, Ru (IEEE International Symposium on Circuits and Systems proceedings, 2020)
This paper proposed a pseudo-open boost DC-DC converter whose input voltage ranges from 300mV-to-500mV and output voltage ranges from 1.2V-to-1.8V. The output power ranges from 1μW to 158μW. Three key structures are designed to realize the high energy conversion efficiency when the load reaches ultra-light: the pseudo open-loop structure, the frequency-programmable oscillator, and the hybrid zero current detection (H-ZCD) circuit. The pseudo open-loop structure eliminates the analog comparators or error amplifiers used in converter and the quiescent power loss is much reduced. The frequency-programmable ring oscillator is able to output 9-bit binary frequency ranges from 500Hz-100KHz, so the power consumption of clock generation is saved when load power reaches to ultra-light. The proposed H-ZCD is designed to reduce the inductor power loss with just tiny power consumption. Accordingly, the high efficiency boost DC-DC works in the discontinuous condition mode (DCM) and the constant on time pulse frequency modulation (PFM) is proposed. As a simulation result, the peak efficiency of the converter reaches to 86.7% while the load power is 13.7μW.